148 Effects of managing mature beef bulls on divergent planes of nutrition on body composition and concentrations of hormones and metabolites. (30th November 2020) - Dahlen, Carl R; Underdahl, Sarah R; Crouse, Matthew S; McCarthy, Kacie L; Kassetas, Cierrah J; Baumgaertner, Friederike; Kirsch, James D; Dorsam, Sheri T; Sedivec, Kevin K; Ward, Alison K; Caton, Joel
Abstract: Fifteen mature beef bulls (BW = 800.4 ± 17.4 kg) were used in a 112-d experiment to evaluate effects of divergent planes of nutrition on body composition and concentrations of hormones and metabolites. Bulls were ranked by BW and randomly assigned to one of two treatments; 1) managed on a positive plane of nutrition (POS, n = 8), or 2) managed on a negative plane of nutrition (NEG, n = 7). Bulls were fed a common diet with deliveries into Insentec feeders adjusted biweekly to achieve targeted weight loss or gain (~12.5% of original BW). Blood samples were collected on d 0, 56, and 112. By design, bull BW was influenced by a treatment × day interaction (P < 0.0001), and POS bulls gained 1.27 ± 0.08 kg/d while NEG lost 0.93 ± 0.08 kg/d. Body condition score and scrotal circumference were similarly impacted by treatment × day interactions (P < 0.0001), both starting similar among treatments, then greater for POS than NEG thereafter. To achieve targeted weight divergence POS bulls (13.8 ± 0.45 kg/d) ate more (P < 0.0001) than NEG (5.1 ± 0.45 kg/d). Body composition was impacted (P ≤ 0.02), with rump fat, rib fat, loin muscle area, and intramuscular fat each increasing in POS and decreasing in NEG. Concentrations of NEFA in serum were greater in NEG bulls at d 56 and 112 compared with POS (treatment × day; P < 0.0001), concentrations of glucose (treatment × day; P = 0.02) were greater for POS bulls, and concentrations of urea were not impacted (P = 0.60). Additionally, concentrations of T3 and T4 on d 112 were greater (P ≤ 0.004) for POS. Our model resulted in altered body composition and profiles of hormones and metabolites which could influence semen on functional, morphological, and molecular levels.